People power the Philippine experience - Pelingon, Fil; Naval, Eddie; Mayuga, Sylvia; Salvador, Eva G.; Constantino, Gerry; Malimban, Froilan; Velez, Jose Mari (Communication Foundation for Asia, 1986)
A compact, comprehensive and moving documentary that traces the roots of people power from the assassination of ex-senator Benigno "Ninoy" Aquino to the 4-day triumph by the Camp Crame and Camp Aguinaldo in EDSA. Witnessed by the whole world, the four fateful days of February 22-25, 1986 changed the history of the Filipino nation.